ESG jako narzędzie stymulujące rozwój zielonej transformacji energetycznej - Benduch, Dorota (PRAWO i WIĘŹ, 2025)
This study aims to analyse the role of Environmental, Social, and Governance (ESG) standards as a legal instrument for stimulating the green energy transition in the European Union, with a particular focus on recent regulatory changes introduced in 2025. Using a doctrinal-legal methodology, the research examines EU legal acts and policy documents. The analysis shows that the „Stop-the-Clock” mechanism (implemented on 3 April 2025 as part of the Omnibus I package, COM(2025) 89), which postpones the reporting obligations for companies subject to the second and third waves of the CSRD until 2028-2029 and raises the qualification thresholds to 1,000 employees, 50 million Euro in turnover, or 25 million Euro in assets (Art. 3(2) of the amended CSRD) - reduces the number of obliged companies by 80%. The study finds that ESG standards serve a dual function: (1) as a capital allocation tool, integrating environmental (E), social (S), and governance (G) criteria into EU investment policy; and (2) as a monitoring mechanism based on mandatory non-financial reporting, which – despite controversies over delays – remains critical to achieving the objectives of the European Green Deal. Furthermore, the analysis underlines that the tension between reducing administrative burdens and ensuring transparency of ESG data requires the systematic harmonization of national legislation with the EU acquis communautaire. Without such coordination, which must take into account ECJ jurisprudence and the implementation of sectoral directives (e.g., RED III Directive), the energy transition will remain fragmented, risking social legitimacy deficits and climate policy regression. The study concludes that companies must strategically use the transition period (2025-2029) to implement ESG data collection systems, which are an indispensable condition for maintaining competitiveness in the context of global technological competition.